A study to assess the contraceptive use among married women of urban slums: a cross-sectional study - Sangra, Sonika; Choudhary, Neha; Narangyal, Akash (International Journal Of Community Medicine And Public Health, 2020)
Background: Family planning services like use of modern contraceptives help the couples to delay pregnancy and avoid the unwanted pregnancies. So, understanding the choice of contraceptives for the underserved couples is a key for provision of family planning services. Objective was to assess the contraceptive use among married women of urban slums using semi-structured questionnaire. Methods: The present observational cross-sectional study was conducted over a period of one month i.e. November 2019 in urban slums of Trikuta Nagar, which is a field practice area of Department of Community Medicine, GMC Jammu. Information was gathered from married females of reproductive age group. 50% of the population was selected randomly by lottery method i.e. 90 females. But at the time of study, only 85 married females could be interviewed. Results: The results show that the maximum females belonged to the 15-25 years age group followed by 26-30 years age group. More than 50% were literate, 42.35% had education upto primary level. More than 50% females were self-employed as they were labourers and rests were home-makers. The duration of marriage of most of the respondent women was 0-5 years and 44.70% of women had three living children. 65.88% women had one year gap between the first two pregnancies. Conclusions: The information, education and communication activities about the advantages of using contraceptives and its side-effects while using these contraceptives need to be increased so as to promote the awareness among females of the urban slums.